2023
DOI: 10.1177/23259671231186972
|View full text |Cite
|
Sign up to set email alerts
|

Failure Rates and Complications After Multiple-Revision ACL Reconstruction: Comparison of the Over-the-Top and Transportal Drilling Techniques

Emre Anil Özbek,
Philipp W. Winkler,
Ehab M. Nazzal
et al.

Abstract: Background: Multiple-revision anterior cruciate ligament reconstruction (ACLR) presents several technical challenges, often due to residual hardware, tunnel widening, malposition, or staged surgeries. Purpose: To compare failure and complication rates between the over-the-top (OTT) and transportal drilling (TD) techniques in patients undergoing surgery for failed revision ACLR. Study Design: Cohort study; Level of evidence, 3. Methods: The medical records of patients with at least 2 revision ACLRs using either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…allografts used, there were 28 anterior tibialis (12.3%), 21 achilles (9.2%), seven BPTB (3.1%) and one IT band (0.4%) with the rest being unspecified (75.0%). Mean graft diameter ranged from 9.05 to 9.9 mm in five studies [9,21,23,25,26] comprising 273 patients that reported values, with three studies [21,23,25] reporting significantly greater values in revision than primary procedures (p < 0.01, p < 0.001, p = 0.001).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…allografts used, there were 28 anterior tibialis (12.3%), 21 achilles (9.2%), seven BPTB (3.1%) and one IT band (0.4%) with the rest being unspecified (75.0%). Mean graft diameter ranged from 9.05 to 9.9 mm in five studies [9,21,23,25,26] comprising 273 patients that reported values, with three studies [21,23,25] reporting significantly greater values in revision than primary procedures (p < 0.01, p < 0.001, p = 0.001).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…R-ACLRs tend to result in worse outcomes than that of primary operations [5,6]. As such, technical aspects of r-ACLR have been studied extensively in the adult literature over the past several years, including optimal graft selection, tunnelling and fixation strategies, and staging [7][8][9]. Up to 90% of paediatric and adolescent patients return to sport after index procedures [10], therefore, it is critical for orthopaedic surgeons to have a comprehensive understanding of the most commonly used operative techniques in both primary and revision ACLR for the skeletally immature population.…”
Section: Introductionmentioning
confidence: 99%